Transformational Leadership and Work Performance of Police Officers in Cambodian Provincial Police Commissariats - Bunchhian Chhoun; Yen Yat (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aimed to assess the relationship between transformational leadership and the work performance of Cambodian police officers in provincial police commissariats. Mixed approaches were used to collect the data by adapting from the multifactor leadership questionnaire (MLQ) and the individual work performance questionnaire – IWPQ. A total of 267 participants were deputy police commissariats, office chiefs, and deputy office chiefs working in the six target provinces – Kompong Cham, Kandal, Koh Kong, Svay Rieng, Banteay Meanchey, and Siem Reap province. The study found similar effects of transformational leadership (14.6%) and transactional leadership (14.5%) on work performance. Police leaders built and strengthened relationships, met needs, encouraged, motivated, and supported subordinates, and used the stick-and-carrot approach to enable the staff to perform their tasks. However, statistics explain the increase in applying transformational leadership trends and the transactional approach in the Cambodian context. This finding implies the necessity of extending transformational leadership practice among police leaders in the current context of Cambodia.